(untitled) (Journal of Shaheed Suhrawardy Medical College, 2026)
Background: Adhesive capsulitis, commonly known as frozen shoulder, is a painful musculoskeletal disorder marked by stiffness and restricted shoulder movement. Conventional treatment often involves pharmacological therapy and exercise rehabilitation. Interferential Therapy (IFT), when combined with these modalities, may enhance recovery outcomes. Objective: To evaluate the effectiveness of IFT in combination with non-steroidal anti-inflammatory drugs (NSAIDs) and therapeutic exercise on pain reduction, functional improvement, and range of motion (ROM) in patients with adhesive capsulitis. Methods: A total of 43 patients with adhesive capsulitis were treated with IFT, NSAIDs (naproxen 500 mg twice daily for 10 days with omeprazole 20 mg for gastric protection), and structured shoulder exercises. IFT was administered using a quadripolar current at 80–120 Hz for 20 minutes per session, with six sessions conducted over 14 days. Assessments were conducted at baseline, 2, 4, and 6 weeks using the Visual Analogue Scale (VAS), Shoulder Pain and Disability Index (SPADI), and goniometric ROM measurements. Results: Significant reductions in pain (VAS: baseline 7.15 → week 6: 2.90) and disability (SPADI: baseline 75.39 → week 6: 23.23) were observed. ROM improved progressively across all planes, with abduction increasing from 80.87° to 129.12°, and flexion from 80.27° to 125.12° by week 6. Internal and external rotation also showed marked improvements. Conclusion: IFT, when combines with NSAIDs and exercise therapy enhance recovery in adhesive capsulitis providing synergistic benefit in pain relief, functional restoration and joint mobility. J Shaheed Suhrawardy Med Coll 2024; 16(2): 53-55